Perencanaan Pembangkit Listrik Tenaga Surya Di Pedesaan Kabupaten Simeulue - Aditya Chandra; Martunis (Aceh Journal of Electrical Engineering and Technology, 2023)
Indonesia's current electrification ratio is 87%, this shows that 8.5 million Indonesians or the equivalent of 2500 villages do not have electricity. Indonesia's geographical location is one reason why there are still many areas that have not been reached by the State Electricity Company (PLN), such as Siumat Island. Siumat Island is an area located on Simeulue Island, Simeulue Regency, East Simeulue District, is one of the areas where people have never experienced the use of electrical energy like other areas in big cities on the island of Sumatra. The electricity network in this area has not yet been entered because the reach of the PLN network to enter remote areas such as Pulau Siumat Village is complicated. After all, getting to Siumat Island from Simeulue Island takes approximately 3 hours by sea. The purpose of this study is to analyze from an economic perspective the construction of a solar power plant for the area. From the results of the discussion using the Calculation method, the Planning, Design and Needs Analysis approach, it was found that planning a solar power plant in Pulau Siumat Village was necessary. As a result, with a total of 62 housing units, 3 public facilities and public lighting, the total power required is 38.675 kW. To meet this need, 320 units of solar panels are needed, 372 units of batteries with a capacity of 12 V 250 Ah, 16 units of charge controllers with a total of 300 Ampere and 3 units of inverters with a capacity of 15 kW with the power to be generated is 40kW or 50 kVA. For the needs mentioned above, a budget of IDR 3,946,184,500 is needed.